Instalasi Ulang Penerangan Listrik di Pondok Pesantren Tarbiyatunnisa Desa Serdang Kulon Kecamatan Panongan Kabupaten Tangerang - Yayuk Suprihartini; Taryana Taryana; Rubby Soebiantoro; Djoko Herwanto; Rini Sadiatmi (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
In today's human life, presumably almost depend on electricity. Some of the things that arise if there is a disturbance in electricity, among others, there is no lighting resulting in darkness at night. Electrical installation installation standards have been regulated in the General Electrical Installation Requirements. Apart from matters relating to the security of the electrical installation network, there are other things that we must pay attention to. This is the standard intensity of illumination. The intensity of room lighting is determined in lux units. The amount of room lighting intensity has been regulated in SNI 03-6575-2001. If the lighting intensity in a room is inadequate, it will cause impaired vision problems. The purpose of this activity is to ensure that the lighting installation meets the standards for both installation safety and lighting intensity. The methods of these activities are lectures, counting and reinstalling lighting installations at the Islamic boarding school. is to calculate the amount of safety, conductor, component specifications, and component layout. In addition, the capacity and number of lamp requirements for each room are calculated. The re-installation is carried out by replacing all electrical networks using standard quality components and installing light points as needed. The conclusion of these activities is that after carrying out these activities the installation becomes safe and the lighting of each room is as needed